NADPH oxidases in the differentiation of endothelial cells. Issue 2 (3rd October 2019) - Hahner, Fabian; Moll, Franziska; Schröder, Katrin
Abstract: The differentiation of stem cells into endothelial cells involves the modulation of highly interconnected metabolic and epigenetic processes. Therefore, the differentiation of endothelial cells is a tightly controlled process, which is adjusted at multiple levels, meaning that even the smallest variation can result in major consequences. Reactive oxygen species (ROS) represent a group of second messengers that can interfere with both metabolic and epigenetic processes. Besides their generation by mitochondria, ROS are produced in a controlled manner by the family of NADPH oxidases. The different members of the NADPH oxidase family produce superoxide anions or hydrogen peroxide. Due to the specific sub-cellular localization of the different NADPH oxidases, ROS are produced at diverse sites in the cell, such as the plasma membrane or the endoplasmic reticulum. Once produced, ROS interfere with proteins, lipids, and DNA to modulate intracellular signal cascades. Accordingly, ROS represent a group of readily available and specifically localized modulators of the highly sophisticated signalling network that eventually leads to the differentiation of stem cells into endothelial cells. This review focuses on the role of NADPH oxidases in the differentiation of stem cells into endothelial cells. Graphical Abstract: